Communication, gender-based violence and suicide - Urra Portillo, Javier (Revista Española de Comunicación en Salud, 2023)
The year 2022 claimed the lives of 49 women as a result of gender violence, while 10 men committed suicide and 9 attempted suicide in Spain. Suicide should not be considered as something separated from gender violence, as the male aggressor builds his world around the traumatic domination of the woman he defines as his own. Women who have experienced intimate partner or ex-partner violence are five times more likely to have suicidal thoughts than those who have not. Gender-based violence affects women’s emotional balance, damages their mental health and is a precipitating factor for suicidal behaviour. In addition, many victims think of death as the only way out of so much suffering. In a context of anguish, depression and hopelessness, induced or provoked suicide occurs, as revealed by psychological autopsies that determine the causal relationship between male abuse and self-harm. Psychological experts must explain the process of mental colonisation, coercive persuasion and paradoxical adaptation syndrome. It is also necessary to point out myths and misconceptions, such as that love can do everything or that there is an obligation to control.
Keywords: gender-based violence; communication; suicide